Normative Analysis of the Application of Balinese Customary Law in Determining Child Adoption - Hakim, Lukman; Rahmawati, Alfi; Akbar, Raihan Aulia; Tamam, Badrut (Jurnal Hukum Indonesia, 2025)
Adoption in Balinese customary law, known as "Nyentanang/Meras Pianak/Meras Sentana," serves to continue the family lineage, especially in the patrilineal family system. Adoption in Balinese society has certain principles that prioritize family relationships and the continuity of customary descent. This study aims to analyze the application of Balinese customary law in the adoption process through a study of Decision Number 214/PDT.P/2024/PN. The main focus of the study is to assess the application of Balinese customary law in court decision-making, examining the conformity between Balinese customary law norms and Indonesian laws and regulations regarding adoption. This study uses a normative legal method with a statutory, case, and conceptual approach. The results of the study show that although Indonesian positive law regulates adoption through government regulations and laws, the application of Balinese customary law in adoption provides flexibility in accordance with local cultural values, which prioritize the continuity of descendants and responsibility in the family. However, there is tension between the unwritten Balinese customary law and the written national law, especially regarding the age of the adopted child, which in Decision Number 214/PDT.P/2024/PN involved a 29-year-old child, contrary to the provisions of national law that regulate the adoption of children under the age of 18. The results of this study emphasize the importance of a balance between the application of Balinese customary law and compliance with positive law in maintaining justice and children's rights, so as to create balanced legal certainty in the adoption process.